Effect of ATP and regulatory light-chain phosphorylation on the polymerization of mammalian nonmuscle myosin II - Liu, Xiong (Proc Natl Acad Sci U S A, 2017)
Addition of 1 mM ATP substantially reduces the light scattering of solutions of polymerized unphosphorylated nonmuscle myosin IIs (NM2s), and this is reversed by phosphorylation of the regulatory light chain (RLC). It has been proposed that these changes result from substantial depolymerization of unphosphorylated NM2 filaments to monomers upon addition of ATP, and filament repolymerization upon RLC-phosphorylation. We now show that the differences in myosin monomer concentration of RLC-unphosphorylated and -phosphorylated recombinant mammalian NM2A, NM2B, and NM2C polymerized in the presence of ATP are much too small to explain their substantial differences in light scattering. Rather, we find that the decrease in light scattering upon addition of ATP to polymerized unphosphorylated NM2s correlates with the formation of dimers, tetramers, and hexamers, in addition to monomers, an increase in length, and decrease in width of the bare zones of RLC-unphosphorylated filaments. Both effects of ATP addition are reversed by phosphorylation of the RLC. Our data also suggest that, contrary to previous models, assembly of RLC-phosphorylated NM2s at physiological ionic strength proceeds from folded monomers to folded antiparallel dimers, tetramers, and hexamers that unfold and polymerize into antiparallel filaments. This model could explain the dynamic relocalization of NM2 filaments in vivo by dephosphorylation of RLC-phosphorylated filaments, disassembly of the dephosphorylated filaments to folded monomers, dimers, and small oligomers, followed by diffusion of these species, and reassembly of filaments at the new location following rephosphorylation of the RLC.